Wady wrodzoneThoracoscopic obliteration of the left atrial appendage in paediatric protein S deficiency and neurological complications – prophylaxis of thromboembolic stroke - Haponiuk, Ireneusz; Nachulewicz, Paweł; Łaniewski-Wołk, Przemysław; Burczyński, Piotr; Maruszewski, Bohdan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
We present a case of minimally invasive surgical thoracoscopic obliteration of an abnormal left atrial appendage in a child with the diagnosis of protein S deficiency syndrome and dilative cardiomyopathy, who previously suffered a peripheral thrombosis with disabling stroke and underwent thrombolytic/anticoagulation treatment. The procedure we introduced was aimed at reducing the risk of further thromboembolic complications. We followed the concept of a prophylactic procedure to reduce the risk of another, potentially more disabling stroke in patients after neurological incidents, which is not unique, e.g. closure of patent foramen ovale or carotid endarterectomy. The digital shape pathological structure of the entire LAA was thoracoscopically doubly ligated with endoscopic loops that were inserted through a separate puncture of the thorax, without complications. There was left a limited margin of the LAA under the area of exclusion because of potential hazard of turning down of the interatrial groove with coronary flow disturbances in the coronary arteries. Short- and mid-term follow-up was determined by intensive physiotherapy for improvement of neurological deficits after previous stroke. Thoracoscopic obliteration of the LAA proved to be a feasible option that can be introduced clinically in the future as an additional minimally invasive palliative procedure in the complex prevention of thromboembolic stroke in paediatric patients.